Consumption Taxes in a Life-Cycle Framework: Are Sin Taxes Regressive? - Lyon, Andrew B.; Schwab, Robert M. (The Review of Economics and Statistics, 1995)
In this paper we construct measures of tax incidence over the life-cycle and compare these measures to traditional measures based on annual data. We show that annual measures of the incidence of taxes on consumption goods may differ from life-cycle measures for three reasons. First, annual measures of income reflect transitory components which should have smaller effects on consumption than permanent changes in income. Second, income measured in a single period differs from lifetime income due to age-related differences in earnings. Third, consumption of certain items follows life-cycle patterns independent of changes in income. Surprisingly, we find that these effects cause almost no change in the assessment of the incidence of taxes applying to the consumption of cigarettes. For alcohol, however, we find that a tax on its consumption is slightly less regressive when measured with respect to lifetime income than when measured with respect to annual income.